Design of IoT-Based Analog kWh Meter Monitoring - Saad, Andi Muhammad; Masa, Muhammad Anas; Abdurrahman, Tanridio Silviati Delfina; Syarifuddin, Andi (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
The PLN officer in charge of recording kWh meters is sometimes unable to photograph them because men discovered that the houses were unoccupied and their fences were locked. Due to these circumstances, the calculation of the current month’s electricity consumption is equated with the previous month, and customers can be harmed. The purpose of this research is to take a physical photo of the kWh meter showing the electrical power consumption and send it to WhatsApp. Firstly, it needs to set the timer on the DS3231, which determines the date for activating the esp32-cam to take kWh meter pictures and upload them to the server. Next, esp8255 downloads those photos from the server. Finally, esp8255 sends them to the WhatsApp application. In this study, the results were obtained in the form of an Internet of Things (IoT)-based smart home device system. The WhatsApp application is a notification media, taking pictures of analog kWh meters in 3–5 seconds with throughput, reliability, and availability values of 189 bps, 96%, and 95.97%, respectively.